2019
DOI: 10.1016/j.jbiomech.2018.11.044
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two global positioning system devices for team-sport running protocols

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A comparison of two global positioning system devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…It can be seen from Figure 5 that in the node surface layout scene, the node surface position of the methods in reference [4] and the methods in reference [5] deviates greatly from the actual position of the node, while the node surface position of the proposed method is close to the actual position of the node. It can be seen that the long-distance real-time positioning effect of the methods in reference [4] and the methods in reference [5] is poor, while the longdistance real-time positioning effect of the proposed method is relatively good.…”
Section: Comparison Of Remote Real-time Positioning Effects Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be seen from Figure 5 that in the node surface layout scene, the node surface position of the methods in reference [4] and the methods in reference [5] deviates greatly from the actual position of the node, while the node surface position of the proposed method is close to the actual position of the node. It can be seen that the long-distance real-time positioning effect of the methods in reference [4] and the methods in reference [5] is poor, while the longdistance real-time positioning effect of the proposed method is relatively good.…”
Section: Comparison Of Remote Real-time Positioning Effects Ofmentioning
confidence: 99%
“…Long-Distance Running. In order to verify the long-distance running remote real-time positioning effect of the proposed method, the proposed method, the methods in reference [4], and the methods in reference [5] were used to compare, and the comparison results of the long-distance real-time positioning effect of different methods are shown in Figure 5.…”
Section: Comparison Of Remote Real-time Positioning Effects Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical demands of hockey may be monitored using wearable miniature electro-mechanical devices, providing both global positioning system (GPS) and inertial measurement unit (IMU) data (Cummins et al, 2013 ). These devices provide distances traveled at different velocities (Willmott et al, 2018 ) and can quantify specific movements such as accelerations, decelerations, or changes of direction (James et al, 2021 ). Since the 2013/2015 rule changes, it has been suggested that players cover a similar total distance (~8,400 m) (Ihsan et al, 2018 ) within the modern game, compared with the historical 70-min format (~8,000–8,500 m) (Lythe and Kilding, 2011 ; Buglione et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%